LEGAL ANALYSIS OF PROTECTION FOR CONSUMERS WHO SUFFERED LOSSES DUE TO THE USE OF SKINCARE PRODUCTS (Based on Law Number 8 of 1999 Concerning Consumer Protection) - Hanafi Dwi Laksono; Aris Prio Agus Santoso; Widi Nugrahaningsih (Penelitian dan Pengembangan Ilmu, 2025)
This study discusses legal protection for consumers who suffer losses due to the use of illegal cosmetics. The focus of the study is directed at the effectiveness of the implementation of Law Number 8 of 1999 concerning Consumer Protection, as well as other regulations related to the supervision of the distribution of cosmetics by the Food and Drug Supervisory Agency (BPOM). The main issues raised are the continued rampant circulation of illegal cosmetics that endanger consumer health, weak supervision, and a lack of public legal awareness. This study uses a normative juridical method with a legislative approach and literature study. The data used comes from primary legal materials in the form of laws and implementing regulations, as well as secondary legal materials such as literature, journals, and previous research results. Data analysis was conducted qualitatively to understand the extent to which consumer protection regulations have provided legal certainty for victims of illegal cosmetics. The results of the study indicate that legal protection for consumers is comprehensively regulated in the Consumer Protection Law and sectoral regulations such as Government Regulation No. 31 of 2019 and BPOM Regulations regarding cosmetic supervision. However, its implementation still faces obstacles such as limited supervision, low law enforcement, and a lack of public awareness to report. Therefore, synergy is needed between the government, BPOM, business actors, and consumers to strengthen legal protection, including providing compensation or redress for losses experienced by consumers.